PENGARUH KEPEMIMPINAN, KEDISIPLINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA NON ASN DINAS PEMADAM KEBAKARAN KABUPATEN SITUBONDO - Ambarwati, Dina Dwi; Wahyuni, Ika; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Situbondo district is one of the small districts located in the eastern part of the island of Java. One of them is the fire department located on Madura Street No. 17 Mimbaan West, Panji, Situbondo. The purpose of this research is to analyze the impact of leadership, discipline and work environment on performance through job satisfaction as a variable intervening on non-ASN fire department of Situbondo district. The total sample used in this study was 58 firefighters in Situbondo district besides the chief. Sampling technique using saturation sampling. Data analysis and hypothesis testing in this study using the Structural Equation - Partial Least Square (PLS-SEM) Model. The results of the direct influence hypothetical test using the Smart PLS 3.0 application, showed that Leadership has a significant positive impact on Employment Satisfaction, Discipline has an significant positive effect on Job Satisface, Working environments have a significant negative impact on Job satisfaction, Leadership significantly negatively impact on Performance, discipline significantly adversely influences Performance, work environment significantly positively impacts Performance, Work satisfaction significantly affects Performance, Leadment significantly influences performance through Job satisfaction.